When he was wicked - Quinn, Julia, 1970- (Quinn, Julia, 1970- Bridgerton series., 2021)
"In every life there is a turning point...For Michael Stirling, London's most infamous rake, that moment came the first time he laid eyes on Francesca Bridgerton. After a lifetime of chasing women...he took one look at Francesca Bridgerton and fell so fast and hard into love it was a wonder he managed to remain standing...Now Michael is the earl and Francesca is free, but still she thinks of him as nothing other than her dear friend and confidant"--